Winning chess : tactics & strategies - Nottingham, Ted.; Lawrence, Al.; Wade, Robert Graham (New Dilhui : New York : Goodwill Publishing, Sterling Pub. Co., 1999)
Presents tactics and techniques for playing chess, including openings, middlegame and endgame strategies, forks, pins, skewers, and examples from the games of world champions.
Includes index.
Keywords: Chess for children -- Juvenile literature; Chess problems -- Juvenile literature; Chess; Chess problems